2016
DOI: 10.1021/acssensors.6b00295
|View full text |Cite
|
Sign up to set email alerts
|

Polymer–Metal Organic Framework Composite Films as Affinity Layer for Capacitive Sensor Devices

Abstract: We report a simple method for sensor development using polymer-MOF composite films. Nanoparticles of NH 2 -MIL-53(Al) dispersed in a Matrimid polyimide were applied as a thin film on top of capacitive sensor devices with planar electrodes. These drop-cast films act as an affinity layer. Sensing studies carried out with methanol vapor using impedance spectroscopy demonstrate that the presence of MOF enhances the overall response and lowers the detection limit compared to MOF-free polymer films and bare devices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…The fabrication of the devices was performed as described previously. 29 Briefly, the active electrode area consisted of aluminum metal stacked between TiN layers over underlying dielectric layer of SiO 2 to mimic the final layer of a typical 140 nm CMOS platform. Devices were processed to obtain meander-patterned planar aluminum electrodes by photolithography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fabrication of the devices was performed as described previously. 29 Briefly, the active electrode area consisted of aluminum metal stacked between TiN layers over underlying dielectric layer of SiO 2 to mimic the final layer of a typical 140 nm CMOS platform. Devices were processed to obtain meander-patterned planar aluminum electrodes by photolithography.…”
Section: Methodsmentioning
confidence: 99%
“… 31 The presence of these MOF particles inside the polymeric matrix alter their physical and chemical properties. 29 , 31 For example, it has been observed from membrane studies that variations of the concentration of MOF particles can lead to alterations in the gas transport and adsorption properties. 31 , 33 Furthermore, upon blending the overall dielectric constant—and hence the electrical polarizability—changes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Sachdeva et al reported the use of a NH 2 -MIL-53(Al)/polyimide composite to fabricate a capacitive sensor for methanol vapor [23]. Devices fabricated with the composite material displayed a lower detection limit as compared to the polymer alone or bare electrodes.…”
Section: Mof-based Gas Sensorsmentioning
confidence: 99%